Kompetensutveckling för chefer : En studie inom Tekniska förvaltningen och Socialförvaltningen - Bergqvist, Diana (2012)
This is an assignment by Luleå commune who offers a range of skills training programs where theprimary goals are to develop human skills in the workplace. The municipality has also developed a “Competence circle” that explains five partial competences, personal, professional, social, strategicand functional. They believe that these competences are important to cover the concept ofcompetence in the workplace.That's why the purpose of this study is to find out if the skills training Luleå offers satisfy managers' needs in the Technical management and Social Services. This study is qualitative, the method has been selected because a qualitative study is most adaptable. Six interviews were conducted including three from each management.It is important to know that competencies can be linked to many aspects of people's lives, such as work, family life, social life and can therefore form the basis for training needs. The requirements for change and development of businesses and products are increasing. It is important for businesses to get a chance to professional development and to include short-term needs, but alsolong-term and directed towards understandable objectives, be strategic and a priority of theorganization. People in employment are expected to have skills that they can develop through training. Own initiative, may be crucial for the result of training entails. Validerat; 20120629 (anonymous)